Evaluation Study of Post-Stage II C.D Blocks - Planning Commission (Planning Commission, 1970)
The Community Development programme was started, with the object of creating a tempo of peoples' participation as supplementary to governmental efforts in improving the social and. economic conditions of the rural people. The programme was started in 55 Community Project are as of India in Octo her, 1952- National Extension Service blocks came into existence in 1953 whore All the now areas selected for development were to continue for three years as N,E,S. blocks for which a budget provision of 4.5 lakhs per block was made.
Programme Evaluation Organisation Planning Commission Government of India